EPC Agenda 2004-10-28 - Academic Senate:::::::::
Educational Policies Committee. Chair Report. Agenda Approved. Minutes of 5/16/19 Approved. President Report. Provost Report. Vice Chair Report. Vice President of Administration and Finance Report. Vice President for Student Affairs Report. Associated Students Report. Statewide Senator Report. Staff Representative Report. Robert's Rules for the Senate. APARC Report. EPC Report. FSAC Report. SAC Report. CFA Report. Lecturers Report. Good of the Order. Group Photo.